Paradigma Baru Peningkatan Kinerja Badan Usaha Milik Daerah (BUMD) - Syafaruddin Alwi (Jurnal Siasat Bisnis, 2002)
The Regional Autonomy policy of the government in Indonesia will give a crucial impact for a regional enterprise owned by the regional government (in short BUMD). In the context of regional autonomy era, the BUMD will be playing a very important role in increasing of financial contribution to the real regional income of the region. The problems are, how will this mission be achieved, and what is the business strategy for improving the regional enterprise performance? By aligning human resource strategy, to business strategy, these problems will be analyzed. Strategic business goals should never be considered without linking them with human resource strategy. Based on human resource perspective, the BUMD will therefore be successful to achieve the mission, when it is managed by professional managers and skilled employees. The BUMD must consider to change organization structure, redesigning job, replace unskilled employee, in order to develop organizational performance. Key words: Badan Usaha Milik Daerah (BUMD), regional enterprise performance